Pioneers of capitalism: The netherlands 1000-1800 - Prak, Maarten; Zanden, Jan Luiten Van; Cressie, Lan (New Jersey Princeton University Press, 2023)
The Netherlands was one of the pioneers of capitalism in the Middle Ages, giving rise to the spectacular Dutch Golden Age while ushering in an era of unprecedented, long-term economic growth. Pioneers of Capitalism examines the formal and informal institutions in the Netherlands that made this economic miracle possible, providing a groundbreaking new history of the emergence and early development of capitalism.